The Existence of the Customs of the Kingdom of Sumedang Larang Padjajaran in the Indonesian Constitution - Penanjung, Rd; Nursyamsudin, Nursyamsudin; Syafrida, Syafrida (Jurnal Hukum Replik, 2024)
Indonesian Customary Law as part of the legal system that has been in force since the Indonesian nation existed is indeed a very valuable scientific wealth because it is excavated and rooted in the socio-culture of the people in Indonesia. The existence of customary law communities in Indonesia is protected by the 1945 Constitution. Customary law community is a society that grows and develops in a social environment. The formulation of the problem, how is the existence of customary law of the Kingdom of Sumedang Larang in the state of Indonesia   and what are the constraints on the implementation of customary law of the Kingdom of Sumedang Larang in the state of Indonesia. The approach used in this study is cocentric and statutory approach. Juridical research uses data from literature research. Conclusion: Inaccordancewith the customary law of the Kingdom of Sumedang Larang in  the Indonesian state administration,  that the Constitutional Rights of the  1945 Constitution are the basic basis for the law that guarantees justice from the decision of the Constitution  Sumedang in 1955 concerning the Decree of Peace and the Letter of Settlement and Acceptance with permanent legal force, was realized with the Sumedang Rukun Wargi Association in Indigenous Peoples with aims and objectives. Constraints  on the implementation of customary law of the Kingdom of Sumedang Larang  in the Indonesian statecraft, reform of the  development of customary law both in rules and laws have not been integrated and have an impact on the division of the nationKey words: Custom, Sumedang Kingdom, Constitution